If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6h + 10c + 4f = 66 Reorder the terms: 10c + 4f + 6h = 66 Solving 10c + 4f + 6h = 66 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4f' to each side of the equation. 10c + 4f + -4f + 6h = 66 + -4f Combine like terms: 4f + -4f = 0 10c + 0 + 6h = 66 + -4f 10c + 6h = 66 + -4f Add '-6h' to each side of the equation. 10c + 6h + -6h = 66 + -4f + -6h Combine like terms: 6h + -6h = 0 10c + 0 = 66 + -4f + -6h 10c = 66 + -4f + -6h Divide each side by '10'. c = 6.6 + -0.4f + -0.6h Simplifying c = 6.6 + -0.4f + -0.6h
| X+(x*.0825)=350 | | -25-n=2(3n-2) | | -8-6x=14-7x | | 52=4(-2x+3) | | -2x+5y=-54 | | 2x(x-3)(x-2)= | | 5-4x-3=-4 | | 3h+2c+f=19 | | -3(2x+4)=24 | | -4(x-2)+x=-4 | | 5x+3-2x=3x+10 | | 348.16+16.96+11.01=y | | 9=-9-2x | | 3x(x+2)(x+4)= | | 51=-3x | | -4x-42=-10 | | 3ex-4+8=10 | | -3(4-2x)+4x=x-21 | | 5(w+3)-(4w+5)=5 | | 7(r-5)(4r-1)=0 | | 66.64+7.42+11.01=y | | 38y+15y+22y+6y+44y+5y= | | 0x=76 | | -11+3x=-(2x-3)-4 | | -9x+76=-32-3x | | 2X*(2X+2)=624 | | 10x^4+19x^3+7X^2=0 | | -18x-6(-0.5)=-33 | | -16+x=5(2-5x) | | -x^4-x^2+6=0 | | -3X^2+24X-9=0 | | 6x^2-3x-84=0 |